國中小啟智班教師知覺專業知能的具備程度及需求情形之研究 A Study on the Levels and Needs of Perceived Professional Competency of Junior High School and Elementary School Teachers of Students with Intellectual Disability - 陳蓉潔 Jung-Chieh Chen; 孫淑柔 Shu-Jou Sun (National Changhua University of Education, 2014)
本研究旨在探討國中小啟智班教師知覺專業知能的具備程度及需求情形，以及不同背景變項的啟智班教師在專業知能具備程度與需求情形的差異。本研究採問卷調查法，以98 學年度任教於臺北市、新北市、桃園縣、新竹縣、新竹市、苗栗縣、臺中市、及彰化縣等八個縣市國中小啟智班教師為研究參與者，以自編問卷為研究工具，共寄發正式問卷1531 份，有效問卷共990 份，可用率為64.7％。研究結果發現啟智班教師知覺專業知能的具備程度前三項依序為：「課程規劃與設計」、「教學能力」、及「基本特教知能」；需求程度前三項依序為：「課程規劃與設計」、「基本特教知能」、及「科技輔具的運用」。而且，啟智班教師專業知能的具備程度和需求程度的落差情形會因任教年資、最高學歷、特教學歷背景的不同而有明顯差異。根據結果本研究建議教育行政單位宜加強啟智班教師課程教材編選和科技輔具的運用能力，以及與普通班教師和相關專業人員的溝通合作。 This study was to investigate the levels and needs of perceived professional competency of junior high school and elementary school teachers of students with intellectual disability, and further probed into the differences in the levels and needs of those teachers with different background variables. A questionnaire survey was conducted on the teachers of students with intellectual disability in junior high schools and elementary schools of Taipei City, New Taipei City, Taoyuan County, Hsinchu County, Hsinchu City, Miaoli County, Taichung City, and Changhua County in the academic year of 2009. The research tool was the questionnaire designed by this study. A total of 1531 questionnaires were distributed and 990 effective samples were retrieved, with a valid return rate of 64.7%.The results found that the perceived professional competencies of teachers of students with intellectual disability, in the order of its level, are "curriculum planning and design", "teaching ability", and "basic special education competency"; the competencies in the order of its needs are "curriculum planning and design", "basic special education competency", and "use of assistive technology". The differences in the levels and needs of perceived professional competency of teachers of students with intellectual disability vary significantly due to the variables of years of teaching, highest education, and educational background in special education. Lastly, this study suggested that the educational authorities should strengthen the compilation of the curriculum materials, using assistive technology, as well as improve the communication and cooperation between the regular teachers and related professionals.